Femtosecond Ti: Sa ultra short-pulse laser irradiation effects on the properties and morphology of the zirconia surface after ageing - Kiyan, Vanessa Harumi (2021)
Femtosecond pulses from a Ti:Sapphire laser were used to irradiate specimens of yttria-stabilised (35% mol) tetragonal zirconia (Y-TZP) with the purpose of studying the effects of the irradiations on their surface properties and morphology after ageing. Zirconia disks were divided into eight groups (n = 32) according to their surface treatment and subsequent ageing: Control: no treatment; sandblasting: Al2O3 sandblasting 50 μm; and ultrashort laser pulses irradiation with 25 μJ pulses, considering two different scanning steps based on the width between two grooves. These groups were duplicated and submitted to ageing. The surfaces were analysed using scanning electron microscopy (SEM), and X-ray diffraction. A finite element analysis, a biaxial flexure test, as well as fractographic and Weibull analyses, were performed. The strengths of the disks were statistically different for the treatment factor, and the principal stresses seemed to be concentrated at the centre of the specimens, as predicted by the computer simulations. Ageing decreased the strengths for all groups and increased the Weibull modulus for the laser group with the 40 μm-width between two grooves. The sandblasting group presented the highest monoclinic phase peak. Although the most significant strength was found within the sandblasting group, the phase transformation was favourable to the laser groups. The Weibull modulus was higher for the laser group with the 60 μm-width between two grooves, confirming the highest homogeneity of its failure distribution. Regardless of the surface treatment, strength was decreased with ageing in all groups. The femtosecond Ti:Sa ultra-short pulse laser irradiation can be suggested as an alternative to the gold standard sandblasting in long-term Y-TZP zirconia rehabilitations, such as crowns and veneers.